Girl abroad - Kennedy, Elle (Bloom Books, an imprint of Sourcebooks, 2024)
"When nineteen-year-old Abbey Bly gets the opportunity to study abroad for a year in London, it's the perfect chance to finally slip out from under the thumb of her beloved but overbearing retired rock star father. She's ready to be free, to discover herself--but first off, to meet the girls she's rooming with. That is, until she arrives at her gorgeous new flat to discover those roommates are actually all boys. Charming, funny, insufferably attractive boys. And off-limits, with a rule against fraternizing between housemates after unwanted drama with the previous girl. Abbey has never considered herself a rulebreaker. But soon, she's lying to her father about her living situation and falling for not one, but two men she can't have: her rugby-player roommate and a broody musician with a girlfriend. Not to mention, her research for school has gotten her tangled in a deeply hidden scandal of a high nobility family, surrounding her in secrets on all sides. If there's any hope of Abbey finding love, answers, or a future in London, she'll have to decide which rules--and hearts--might be worth breaking."--Amazon.